Real Estate Price Factors and Economic Efficiency : An Empirical Study Based on Panel Data from 30 Chinese Provinces, 2009–2023 - Wu, Yanping (2025)
China’s land-finance-driven growth model has played a central role in economic expansion since the 1990s, yet its long-term impact on economic efficiency remains uncertain. This study investigates how housing price growth, fiscal expansion, and debt accumulation interact to influence China’s macroeconomic efficiency. Drawing on the Fiscal Expenditure Scale Theory and Endogenous Growth Theory, the analysis constructs a panel model based on provincial data from 2009 to 2023 to examine the effects of real-estate price dynamics on total factor productivity (TFP) and the Malmquist productivity index. The empirical results reveal that rising housing prices significantly reduce economic efficiency. Both baseline and IV-2SLS estimations confirm a persistent and nonlinear negative relationship between housing prices and productivity growth, suggesting that efficiency loss intensifies when housing prices exceed a certain threshold. Heterogeneity analysis shows that this negative effect is most pronounced in the Yangtze River Economic Belt and the five major urban agglomerations, where advanced industrialization and fiscal dependence amplify the fiscal–financial distortions associated with land finance. Further, moderation effect tests demonstrate that government, corporate, and household debt all exacerbate the negative impact of housing price expansion on productivity. Among them, government leverage closely linked to land-transfer revenues plays the dominant role, forming a fiscal–financial feedback loop that weakens the efficiency of capital allocation. Robustness tests using alternative housing price measures and additional control variables confirm the stability of the results. The findings contribute to the understanding of how fiscal structures and real-estate cycles jointly shape economic efficiency in transitional economies.